Antigenic conservation of an immunodominant invariable region of the VlsE lipoprotein among European pathogenic genospecies of Borrelia burgdorferi SL - Liang, Fang Ting; Aberer, Elisabeth; Cinco, Marina; Gern, Lise; Hu, Chang Min; Lobet, Yves; Ruscio, Maurizio; Voet, Pierre; Weynants, Vincent; Philipp, Mario T (My University, 2000)
Lyme disease is caused by genetically divergent spirochetes, including 3 pathogenic genospecies: Borrelia burgdorferi sensu stricto, B. garinii, and B. afzelii. Serodiagnosis is complicated by this genetic diversity. A synthetic peptide (C-6), based on the 26-mer invariable region (IR6) of the variable surface antigen of B. burgdorferi (VlsE), was used as ELISA antigen, to test serum samples collected from mice experimentally infected with the 3 genospecies and from European patients with Lyme disease, Regardless of the infecting strains, mice produced a strong antibody response to C-6, which indicates that IR6 is antigenically conserved among the pathogenic genospecies. Twenty of 23 patients with culture-confirmed erythema migrans had a detectable antibody response to C-6, A sensitivity of 95.2% was achieved, with serum samples collected from patients with well-defined acrodermatitis chronica atrophicans, Fourteen of 20 patients with symptoms of late Lyme disease also had a positive anti-IR6 ELISA, Thus, it is possible that C-6 may be used to serodiagnose Lyme disease universally.
Keywords: OUTER SURFACE-PROTEIN; CHRONIC NEUROLOGIC MANIFESTATIONS; ERYTHEMA; MIGRANS BORRELIOSIS; STANDARDIZED WESTERN BLOTS; LYME-DISEASE SEROLOGY; SENSU-LATO; INTERPRETATION CRITERIA; IMMUNE-RESPONSE; DIAGNOSIS; SERODIAGNOSIS